Carbon monoxide oxidation over platinum: Stable, oscillatory and quasi-chaotic regimes - Lagos, Roberto E. [UNESP]; Simões, Tania [UNESP]; Godoy, Adolfo L. (Elsevier, 1998)
We model the heterogeneously catalyzed oxidation of CO over a Pt surface. A phase diagram analysis is used to probe the several steady state regimes and their stability. We incorporate an experimentally observed 'slow' sub-oxide kinetic step, thereby generalizing a previously presented model. In agreement with experimental data, stable, oscillatory and quasi-chaotic regimes are obtained. Furthermore, the inclusion of the sub-oxide step yields a relaxation oscillation regime. © 1998 Elsevier Science B.V. All rights reserved.
Keywords: Bifurcations; Chaos; Chemical oscillations; Relaxation; Bifurcation (mathematics); Carbon monoxide; Catalysis; Chaos theory; Chemical relaxation; Mathematical models; Oscillations; Platinum; Reaction kinetics; Relaxation oscillators; System stability; Quasi-chaotic regimes; Oxidation